Women Welfare Safety and Prevention System - Daya Florance, D; Malleswari, M; Ragunapriya, V; Renuka Devi, R (International Journal of Engineering and Technology, 2018)
In a recent time, the performance of hitting and inhumanity against women increasing at an unpredictable rate. It is an essential thing for females to travel from some place to another place at late night and visiting distance places and obscure places as a segment of their work. Anyways, the rapid increase in hitting the women safety and criticizing the women in the last few decades constitutes a menacing to the extension and evaluation of female. Protection is the only issue that can adequate to against this expanding abuse. A women safety and security mobile application that develops a secure feeling between female required to be plan need to heart beat sesnor for auto sense are deployed atÂ the wrist sensing . A requirement of basic safety resolution that can be done in a simple method, when the women touches the button, then immediately the Sms alert will send to the guardian which is the contact that is alreadystored in the mobile application. In this paper we intend to design and implementation such a system.